Synthesis of Fly Ash-Based Geopolymers Using Various Alkali Activators for Dye Removal - Wan Abdul Halim, Wan Maizatul Fathirah (IRC, 2016)
The presence of large quantities of dyes in the wastewater has garnered more attention to the world as they can possess harmful effects both to the human beings as well as to the living organisms. Almost every products and foods that we consume daily consist of dyes, thus making the amount of dyes being released into the wastewater keeps increasing year by year. Various types of adsorbents have been synthesized in order to overcome this problem. The discovery of geopolymers as a potential adsorbent is significant due to its amorphous and porous structure. In this study, geopolymers synthesized from fly ash were used as the adsorbent.